2013
DOI: 10.1371/journal.pone.0068142
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Water Oxidizing Complex of Photosystem II and the Reoxidation of the Quinone Acceptor QA− by Pb2+

Abstract: The action of the environmental toxic Pb2+ on photosynthetic electron transport was studied in thylakoid membranes isolated from spinach leaves. Fluorescence and thermoluminescence techniques were performed in order to determine the mode of Pb2+ action in photosystem II (PSII). The invariance of fluorescence characteristics of chlorophyll a (Chl a) and magnesium tetraphenylporphyrin (MgTPP), a molecule structurally analogous to Chl a, in the presence of Pb2+ confirms that Pb cation does not interact directly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…This is also reflected in the decrease in the number of active reaction centers per cross section (RC/CS 0 ). In PsbA protein, lead often associates with Q B site preventing electron transport between Q A and Q B sites but also beyond Q B [30,61]. In case of P. zeylanica shoots, we noted decrease of ϕ Po and increase of ψ Eo , what informs on the one hand about reduced electron flow efficiency between Q A and Q B and on the other hand about the increase of probability that trapped exciton moves an electron beyond Q B in these plants.…”
Section: Discussionsupporting
confidence: 50%
“…This is also reflected in the decrease in the number of active reaction centers per cross section (RC/CS 0 ). In PsbA protein, lead often associates with Q B site preventing electron transport between Q A and Q B sites but also beyond Q B [30,61]. In case of P. zeylanica shoots, we noted decrease of ϕ Po and increase of ψ Eo , what informs on the one hand about reduced electron flow efficiency between Q A and Q B and on the other hand about the increase of probability that trapped exciton moves an electron beyond Q B in these plants.…”
Section: Discussionsupporting
confidence: 50%
“…(2) On the PSII RC—substitution of Mg 2+ by Pb 2+ in the chlorophyll porphyrin ring, what is very dangerous especially in PSII RCs and antenna systems (Harpaz-Saad et al 2007 ). (3) On the acceptor side—substitution Fe 2+ by Pb 2+ in protonation complex which is responsible for the protonation of the semichinol radical Q B − (Belatik et al 2013 ). Since chl a fluorescence measurement is a useful, non-invasive, and reliable method for estimation of heavy metal impact on photosynthetic apparatus (Papageorgiou et al 2007 ; Kodru et al 2015 ; Stirbet et al 2014 ; Kalaji et al 2016 ), the fast fluorescence chl a kinetics test was used to assess the condition of Anthyllis vulneraria photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already pointed out that PSI is particularly sensitive to heavy metal stress (Wodala et al 2012), as well as to other oxidative stress factors (Bussotti et al 2011;Mereu et al 2011;Salvatori et al 2014). Moreover, it has been recently shown that Pb 2+ is able to interact with PSI at the plastocyanin (PC) level, thus specifically inhibiting the electron transfer process at the PSI donor side (Belatik, Hotchandani and Carpentier 2013). Although in our experiment the Pb concentration in leaves was relatively low (88.8 ± 11.3 mg kg -1 ), it was 50.7% more than the control, therefore the persistence of the I-P phase alteration after the recovery of gas exchanges suggests that such phytotoxic effects at the leaf level cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%